Philippine mineral resources towards the HORIZON: A webinar series on mineral resources management - Center for Engineering and Sustainable Development Research (Animo Repository, 2021)
CENTER FOR ENGINEERING AND SUSTAINABLE DEVELOPMENT RESEARCH Waste and Resource Management Unit cordially invited the (students, faculty and researchers) to attend the webinar series “Philippine Mineral Resources towards the HORIZON: A Webinar Series on Mineral Resources Management” SAGES: Systems Approach for Greener, Eco-efficient, and Sustainable mineral resource management project on 17th September 2021, Friday 10:00 AM–12:00nn The second series focused on Sustainability and the Theory of Change in Mining.